ANALISIS KADAR EMISI TRANSPORTASI DI SAMARINDA BERDASARKAN TIPE MESIN DAN KAPASITAS MESIN - Yanti, Derli; Mislan, Mislan; Djayus, Djayus (GEOSAINS KUTAI BASIN, 2020)
Transportation emission levels can be analyzed based on the type of engine used. The purpose of this study is to determine the level of vehicle emissions each year and compare in samarinda. This research was conducted by measuring air emissions in different tool brands, the sukyoung SY-GA 401 brand used was the type of injection engine and carburetor, and the AGS-688 brand used was a diesel / diesel engine type where the measurement of the emission levels used the tool Automotive Emission Analyzer. Data was collected at the Kesuma Bangsa, Slamet Riyadi, and Wahid Hasyim points in 2013, 2014, 2015, 2016, 2018 in samarinda region known data on air emission levels, namely: Total pollutants of carbon monoxide (CO), carbon dioxide (CO2), carbon monoxide correction (COcorr), hydrocarbons (HC), oxygen (O2) and lambda (λ). The results showed that the analysis of air emission levels with the highest type of pollutant injection machine, namely HC in 2015 was 107.82 ppm based on the quality standard limits set by LH regulation No 05 of 2006 did not exceed the quality standard threshold of 200 ppm, pollutant carburetors the highest was found in HC pollutants in 2015 amounting to 434.35 ppm exceeding the quality standard threshold of 200 ppm and the highest solar pollutants were in the opacity pollutants in 2015 of 80.28% HSU based on the quality standard threshold stipulated by LH Regulation 05/2006 exceeding the quality standard threshold of 70% HSU.